Optimization of The Slope Angle of a Submerged Piezoelectric on a Laboratory Scale - Wardhana, Ede Mehta; Ditya, Danang Jawara; Ilyasa, Farhan (International Journal of Marine Engineering Innovation and Research, 2024)
Piezoelectrics are materials that can produce electrical voltage when subjected to mechanical stress. This unique property makes piezoelectrics widely used in various applications, such as sensors, actuators, and transducers. One important factor that can influence piezoelectric performance is the tilt angle. The tilt angle is defined as the angle between the piezoelectric surface and the direction of the applied force. This research aims to optimize the tilt angle of immersed piezoelectrics on a laboratory scale. Using the experimental method, this research was carried out using piezoelectric PVDF. Piezoelectric PVDF was chosen because it has good piezoelectric properties and is easy to obtain. Experiments were carried out by applying mechanical force to the piezoelectric PVDF with various tilt angles. Experimental results show that the optimal tilt angle for submerged piezoelectric PVDF is 90 degrees with a value of 7.46196 milliVolts at a flow speed of 1.2m/s. At this tilt angle, the piezoelectric PVDF produces the highest electrical voltage. The results of this study indicate that the optimal tilt angle for sunken piezoelectrics is 90 degrees. This could provide a basis for the development of more efficient and high-performance piezoelectric designs.